Anticoagulation Management in Patients with Atrial Fibrillation in a Spanish Region: Results of the RUFIAN Registry (Revista de Medicina Clinica, 2023)
Introduction: Main characteristics of patients with Atrial Fibrillation treated and hospitalized in the Internal Medicine Services of the Canary Islands (Spain), as well as the management of anticoagulation based on their clinical profile. Patients and methods: Observational, prospective, study conducted in the main public hospital in Gran Canaria (Spain). All nonvalvular Atrial Fibrillation patients attended in the Emergency Service and admitted in Internal Medicine (2014-2016) were included in the RUFIAN registry. Routine NVAF management was collected through the medical records. Results: The study sample was formed by 905 NVAF patients (12.8% de novo). The mean age was 80.7(8.2) years old, 52.9% were male and 24.3% had severe chronic kidney disease (CKD). Arterial hypertension and heart failure were the main comorbidities observed (89.9% and 77.7%). Mean CHA2DS2-VASc was 4.8(1.4) and HAS-BLED was 2.5 (1.2). During the Emergency visit, 56.9% of the patients were anticoagulated and 41.2% received antiplatelet therapy (59.9% and 53.5% in severe CKD patients, respectively). At hospital discharge, anticoagulation was 56.0% and antiplatelet therapy decreased to the 35.4% of the patients (44.8% and 28.7% in severe CKD patients, respectively). In-hospital mortality was 13.6%, ranging from 11.1% in patients
Keywords: Atrial fibrillation; Anticoagulants; Registries; Evidence-Based Practice; Spain